Three tools to visualize and prevent boilers and furnaces firebox explosions. Issue 3 (29th July 2017) - Fernández Blanco, Roberto
Abstract : Explosive incidents with harmful consequences continue to occur in boilers and furnaces (heaters) where fossil fuels are burned. Proper designs, proper maintenance, and proper operating procedures have been developed, backed by standards, codes, guidelines, and recommended practices. However, process knowledge (education) and appropriate operating and maintenance procedures (training) remain the essential tools for personnel to understand the circumstances leading to catastrophic consequences and thus be able to enhance the safety conditions of combustion processes. Tackling the root of this problem requires visualizing the associated concepts, rules, and cautions to fully understand the nature of combustion, foresee its hazards, and prevent incident outcomes and consequences. This article is intended to provide colleagues in the field, engineers, technicians, and operators—who, on a daily basis, live in close proximity to the risks of fossil‐fired boilers, furnaces, gas turbines, heaters, and processes with flammable mixtures—three basic tools to allow them to visualize, and thus, find it easier to remember, the concepts associated with the hazards of combustion processes by reviewing the knowledge available to prevent explosive incidents. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 221–236, 2017